Correlation Between Knowledge And Attitudes Of Young Women About Anemia With Adherence In Taking Blood Supplement Tablets - Yustina, yusniawati; Ni Nyoman Nuartini; Sri Mas Utami, Ni Putu Listya (JURNAL KESEHATAN PRIMER, 2025)
Background: Iron deficiency anemia is a lack of erythrocyte supply to perform erythropoiesis, which eventually causes a decrease in Hb. In Tabanan District (98.52%) of adolescents received blood supplement tablets, but only (95.77%) of adolescents took blood supplement tablets. Research needs to examine the correlation between adolescents' knowledge and attitudes with adherence in taking blood supplement tablets. To determine the correlation knowledge level and attitudes of young women about anemia with adherence in taking blood supplement tablets. Methods: This study employed analytic correlation study with cross-sectional approach, with 151 young women recruited as sample of the study which were selected through total sampling technique. The data were collected by using questionnaire and analyzed by using Spearman-Rho statistical test. Results: The finding showed that there were 81 respondents (53.6%) had good knowledge and there were 125 respondents (82.8%) had positive attitude about anemia. The majority of young women adherence was in the high category as many as 82 (54.3%). There is a significant correlation between the level of knowledge and attitudes about anemia with adherence in taking blood supplement tablets (p < 0.05). Conclusion: The higher the knowledge about anemia and the more positive the attitude, the higher the adherence of young women in taking blood supplement tablets.